CHANGES IN PROTEIN METABOLISM OF ALBINO RATS AT INDUCED AMMONIA STRESS - A.SIREESHA,; P. NEERAJA, (International Journal of Pharma and Bio Sciences, 2013)
The present study aims at understanding the alterations in the protein metabolism of albino rats at induced ammonia stress. Albino rats were induced to sub lethal dose of 1.16 ppm of ammonium sulphate until delivery. The total proteins, free amino acids, urea, ammonia and arginase activity were estimated in tissues of brain, liver and kidney in male, female and litters. The changes in these parameters were discussed.